Legal Protection for Women Victims of Trafficking in Indonesia in an International Human Rights Perspective - Rai Yuliartini, Ni Putu; Sudika Mangku, Dewa Gede (International Journal of Criminology and Sociology, 2022)
The research aims to analyze the legal protection of women victims of trafficking in Indonesia in an international human rights perspective. The type of research used is empirical normative legal research. The data obtained from this study is primary and secondary data obtained from the results of field research and literature analyzed and reviewed its legal relevance and used to decipher conceptions and theories used in this study, then the data obtained is analyzed qualitatively through a statute approach and conceptual approach. The results of this study show that the legal protection of women victims of people trafficking in the perspective of International Human Rights is found in Act of number 21/2007 about the Eradication of People Trafficking Crimes, but the provision of a form of protection against female victims is not supported by implementing regulations, such as government regulations.